Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.3354/meps085203
|View full text |Cite
|
Sign up to set email alerts
|

Export production and the distribution of fish larvae and their prey in a coastal jet frontal region

Abstract: Fine-scale spatial sampling series and vertical cross-sections were used to obtain quasisynoptic images of the distribution of fish larvae and their prey in the permanent frontal region formed by the Gaspe coastal jet current and the adjacent Anticosti gyre (NW Gulf of St. Lawrence, Canada). The accumulation of large diatoms triggered the reproduction of copepods in the Gasp6 current where eggs and nauplii (the main prey of first-feeding fish larvae) were 10 to 20 times more abundant than in the gyre. Estuarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
5
30
0
1
Order By: Relevance
“…These areas are characterised by large spatial variability in key physical parameters such as temperature and salinity (Fortier et al 1992, Lochmann et al 1997, Lee et al 2005, and here we often observe enhanced primary production, due to upwelled nutrients, and enhanced concentrations of zooplankton and fish larvae, partly due to converging currents and concentration of non-passive organisms (LeFevre 1986, Franks 1992, Franks & Chen 1996, Aretxabaleta et al 2005. Specific physical and biological measures vary markedly within relatively short distances across frontal zones (< 5 km), and both field observations (e.g.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…These areas are characterised by large spatial variability in key physical parameters such as temperature and salinity (Fortier et al 1992, Lochmann et al 1997, Lee et al 2005, and here we often observe enhanced primary production, due to upwelled nutrients, and enhanced concentrations of zooplankton and fish larvae, partly due to converging currents and concentration of non-passive organisms (LeFevre 1986, Franks 1992, Franks & Chen 1996, Aretxabaleta et al 2005. Specific physical and biological measures vary markedly within relatively short distances across frontal zones (< 5 km), and both field observations (e.g.…”
Section: Introductionsupporting
confidence: 57%
“…Differential growth and thereby differential mortality has implications for the interpretation of larval concentrations in frontal zones. The frequently observed aggregations of plankton organisms are mainly attributed to localised spawning behaviour of adults and accumulation due to an interplay of converging currents and vertically migrating behaviour of plankton organisms (Fortier et al 1992, Franks 1992. However, no firm conclusion has been reached on the influence of differential mortality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Les larves ont également une faible capacité natatoire et leurs déplacements sur de longues distances consistent principalement au transport passif des courants marins. Dans certains cas, on observe une migration verticale leur permettant d'accéder à des courants plus favorables (Grioche et al, 2000), mais en général les courants créent une dispersion spatiale des larves pouvant les éloigner des zones productives nécessaires à leur survie (Iles & Sinclair, 1982;Fortier et al, 1992).…”
Section: Gestion Des Pêchesunclassified
“…However, that ecosystem has marked océanographie and biological differences compared with the northwest GSL, which shows a zooplankton community typical of the sub-arctic northwest Atlantic dominated by Calanus species both in abundance and biomass and high abundance of much smaller Oithona (De Lafontaine et al, 1991;Plourde et al, 2002;Harvey and Devine, 2009). In the GSL, Fortier et al (1992) partially described the larval diet of arctic shanny, but indicated developmental stages only, without giving prey species identification; hence, very little is known about the feeding ecology of arctic shanny and snakeblenny larvae. Furthermore, since many studies have indicated that larval feeding selectivity and copepod escape response are dependent on species and developmental stage (Fields and Yen, 1997;Buskey et al, 2002;Visser, 2007;Robert et al, 2008), the detailed identification of prey species should be considered in the evaluation of feeding selectivity by fish larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation